MY SAY: Of flying pigs and human error - Abd Razak, Dzulkifli (2009)
The number of confirmed cases of "swine flu", or more recently renamed influenza A (H1N1), has passed the 10,000 mark worldwide, according to the World Health Organization (WHO). This has triggered WHO to raise its pandemic alert to "Phase 5". This level "is characterised by human-to-human spread of the virus into at least two countries in one WHO region". The Phase 5 alert is a strong indication that a pandemic is imminent. While some criticised the world body for being hasty, others felt that it is better to err on the side of caution rather than be sorry. Moreover, there is the possibility that the flu may come back with a vengeance during the onset of the Northern Hemisphere winter.